A Narrative Inquiry into an Army School Leadership Experience - Smith, Kyle (My University, 2016)
The focus of this study is to reconstruct meaning through an interpretation of change on who I am and what I am becoming, navigating through a pervasive space that encompasses temporal, personal/social, and place creating knowledge from the lived experience (Clandinin, 2013). The personal stories explored permit the reader an ability to construct broader frames of reference and discover important assumptions and theories that guide leadership actions (Mattingly, 1991). As the primary researcher, I sought to contribute to the body of research surrounding Army educational leadership practice, particularly by exploring gaps along the Army leader development model in relation to school leadership preparation, selection, education and fractured purpose. I reviewed critical events that guided my past as both an Army leader and more recently, as an Army educational leader situated at a Center of Excellence containing two branch/proponent schools. I collected data primarily through field texts, calendar events, recollections, white papers, and recounting my own lived experiences. Findings explored my professional development as an Army leader, educational leader, and researcher along leadership and policy issues encompassing Army school leadership gaps. Theory is weaved throughout the study explaining what is going on in the practice. A rich account of my experience creating knowledge from the lived experience is described narratively to inform those attempting similar changes.
Keywords: Administration, Army, Educational Leadership